2015
DOI: 10.1016/j.tsf.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependence of the structure and ferroic properties of epitaxial Ni1−xTi1−yO3 thin films grown on sapphire substrates

Abstract: Polarization-induced weak ferromagnetism has been predicted a few years back in compounds MTiO 3 (M = Fe, Mn, Ni) (Fennie, 2008). We set out to stabilize this metastable, distorted perovskite structure by growing NiTiO 3 epitaxially on sapphire Al 2 O 3 (001) substrate, and to control the polar and magnetic properties via strain. Epitaxial Ni 1 − x Ti 1 − y O 3 films of different Ni/Ti ratios and thicknesses were deposited on Al 2 O 3 substrates by pulsed laser deposition at different temperatures, and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Al 2 O 3 substrate was chosen as a nonmagnetic, nonpolar alternative with lattice parameters close to those of NiTiO 3 , but still providing a large positive (5.7%) lattice mismatch and thus compressive strain. Sapphire substrates have been used previously to grow epitaxial FeTiO 3 films [29] and, more recently, epitaxial NiTiO 3 films [9,11,30]. The potential benefit to using sapphire substrate may be the considerable compressive strain it provides, which may mimic a high-pressure compression employed in the synthesis of bulk LNO-type FeTiO 3 [5] and MnTiO 3 [7].…”
Section: Influence Of Strain On the Structural And Morphologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Al 2 O 3 substrate was chosen as a nonmagnetic, nonpolar alternative with lattice parameters close to those of NiTiO 3 , but still providing a large positive (5.7%) lattice mismatch and thus compressive strain. Sapphire substrates have been used previously to grow epitaxial FeTiO 3 films [29] and, more recently, epitaxial NiTiO 3 films [9,11,30]. The potential benefit to using sapphire substrate may be the considerable compressive strain it provides, which may mimic a high-pressure compression employed in the synthesis of bulk LNO-type FeTiO 3 [5] and MnTiO 3 [7].…”
Section: Influence Of Strain On the Structural And Morphologicalmentioning
confidence: 99%
“…Recently, we have demonstrated that epitaxial NiTiO 3 films can be grown on sapphire substrate by PLD [9] and that such films exhibit both lattice polarization and weak ferromagnetism [10]. Furthermore, the properties of NiTiO 3 / Al 2 O 3 films were successfully manipulated by applied strain [11]. While the latter reports confirmed that our epitaxial NiTiO 3 films were indeed of the LNO-type structure, the lattice mismatch between the film(s) and the sapphire substrate resulted in less-than-high-quality films in terms of crystallinity, most likely affecting the observed physical properties 2 Advances in Condensed Matter Physics adversely.…”
Section: Introductionmentioning
confidence: 99%
“…Although FeTiO3 has been synthesized with the LiNbO3 structure at high pressure, [137,138] this polymorph has not been unambiguously observed for NiTiO3. [139][140][141] Determining if the symmetry is R−3c or R3c is hard with X-ray diffraction alone. The difference in unit cell parameters between such polymorphs is small and effects from strain and off-stoichiometry is likely to a If not removed, the native SiO2 layer on Si inhibits epitaxial growth.…”
Section: Growth Of Nitio3 On Oxide Single Crystal Substratesmentioning
confidence: 99%
“…lattice polarization was observed, and possibly weak ferromagnetism, indicating the presence of the LiNbO3 structure [11][12][13]. Ferroelectricity and weak ferromagnetism have indeed been observed in bulk samples of NTO as well [14], but the report did not discuss the crystal symmetry of the samples.…”
Section: Introductionmentioning
confidence: 92%
“…Ferroelectricity and weak ferromagnetism have indeed been observed in bulk samples of NTO as well [14], but the report did not discuss the crystal symmetry of the samples. Thin films of NTO have previously been made by various deposition techniques, including aerosol-assisted CVD [2], sol-gel methods [3,[15][16][17][18], dip-coating [19] and RF-sputtering [4,5], as well as with the previously mentioned pulsed laser deposition [10][11][12]. Especially for the latter technique, compositional control seems to be challenging.…”
Section: Introductionmentioning
confidence: 99%